Augmented reality for orthopedic and maxillofacial oncological surgery: a systematic review focusing on both clinical and technical aspects - Nasir, Naqash; Cercenelli, Laura; Tarsitano, Achille; Marcelli, Emanuela (Frontiers in Bioengineering and Biotechnology, 2023)
This systematic review offers an comprehensive overview of on clinical and technical aspects of augmented reality (AR) applications in orthopedics and maxillofacial oncological surgery, focusing on both clinical and technical aspects. The review also provides a summary of the included articles with objectives and major findings for both specialties. The SPIDER (Sample, Phenomena of Interest, Design, Evaluation, Research type) method was used to construct a suitable research question. The search was conducted on PubMed/Medline and Scopus databases and returned on 31 May 2023. All articles of the last 10 years found by keywords related to augmented reality, mixed reality, maxillofacial oncology and orthopedics oncology were considered in this study. For orthopedics oncology, a total of 9344 articles were found and only 9 articles were selected following the defined inclusion criteria. These articles were subclassified further based on study type, AR display type, registration/tracking modality and involved anatomical region. Similarly, out of 95886 articles on maxillofacial oncology, 271 articles were selected for this review and categorized further in the same manner. Main The main outcomes reported for both specialties are related to registration error (i.e. how the virtual objects displayed in AR appear in the wrong position relative to the real environment) and surgical accuracy (i.e. resection error) obtained under AR navigation. However, meta-analysis on these outcomes was not possible due to data heterogenicity. Despite having certain limitations related to the still immature technology, we believe that AR is a viable tool to be used in oncological surgeries of orthopedics and maxillofacial field, especially if it is integrated with an external navigation system to improve accuracy. It is emphasized further to conduct more research and pre-clinical testing before the wide adoption of AR in clinical settings.